A Feminist stylistic analysis of women characters in The Night Monkeys perspectives from M.A.K. Halliday - Grande, Maria Theresa R.; Laurel, Ma. Milagros C. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2014)
The paper analyzed award-winning short stories for children in the Don Carlos Palanca Memorial Awards for Literature. Specifically, it focused on the representation of the principal female characters in the short stories from the anthology The Night Monkeys: More Palanca Prize Winners for Children using M.A.K. Halliday's Transitivity Model of Analysis. Seven stories were examined for the study. Verb choices served as the basis for determining character's representation. The action processes expressed by the verb choice showed the principal female characters as active characters. However, a closer examination of the transitivity relations led to a different conclusion, that is, that while these female characters were the actors, and therefore, seemingly the active participants in each of the texts that were analyzed, these same female characters were doing the action to themselves or to non-conscious recipients. Thus, through M.A.K. Halliday's method of analysis of the processes revealed by the verb choices, the study was able to present an insightful portrayal of the principal female characters in the Palanca award-winning short stories for children.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.